Contingency, hegemony, universality contemporary dialogues on the left - Butler, Judith 1956-; Laclau, Ernesto 1935-2014; Zizek, Slavoj (Phronesis (London, England)., 2000)
"What is the contemporary legacy of Gramsci's notion of hegemony? How can universality be reformulated now that its spurious versions have been so thoroughly criticized? "In this ground-breaking project, Judith Butler, Ernesto Laclau and Slavoj Zizek engage in a dialogue on central questions of contemporary philosophy and politics. Their essays, organized as three contributions each that respond to one another, range over the Hegelian legacy in contemporary critical theory, the theoretical dilemmas of multiculturalism, the universalism-versus-particularism debate, the strategies of the left in a globalized economy, and the relative merits of post-structuralism and Lacanian psychoanalysis for a critical social theory." "While the rigour and intelligence with which Butler, Laclau and Zizek approach their work is as formidable as one would expect, Contingency, Hegemony, Universality benefits additionally from their clear sense of energy and enjoyment in a revealing and often unpredictable exchange.Book jacket."--Jacket.